Gastric cancer screening in Chile. Results of the National Health Survey 2016-2017 - Corsi Sotelo, Oscar (2025)
Introduction: Gastric cancer (GC) is the leading cause of oncologic death in Chile. Since 2006, the health authority has recommended upper gastrointestinal endoscopy (UGE) for symptomatic individuals ≥40 years old. In 2010, the UGE coverage in this group was estimated at 14%. Objective: To evaluate UGE coverage for GC screening in Chile using data from the National Health Survey (NHS) 2016-17. Materials and methods: The NHS 2016-17 surveyed 6,233 adults about the presence of persistent epigastric pain, possible upper gastrointestinal bleeding, and UGE. UGE prevalences among different groups were compared, and multivariate models adjusted for sex, age, income, education, area of residence, and belonging to an indigenous group were constructed. Results: Both persistent epigastric pain and possible upper gastrointestinal bleeding were reported by 4.7%, being higher in the ≥ 40-year-old group and lower educational level. The prevalence of UGE performed at least once in life reached 20.8%, being higher in women, ≥40 years old, privately insured individuals, and the non-indigenous Hispanic population. The coverage of UGE in the last year among symptomatic individuals ≥40 years old increased to 19.8%, with no significant differences in the multivariate analysis. Conclusion: The coverage of UGE in the last year in symptomatic individuals ≥40 years old for GC screening in Chile is 19.8%. Lowest socioeconomic status and indigenous peoples are disadvantaged groups.